Molar enthalpy and heat capacity for symmetric trigonometric Rosen-Morse plus Pὂschl-Teller potential - C.A. Onate; J.A. Akinpelu; O.O. Ajani; B.B. Deji-Jinadu; F.O. Aweda; J.B. Fashae; O.O. Jegede (South African Journal of Chemical Engineering)
Some potential models are only studied for open systems even though applied to certain models, the theoretical value cannot be justified by the observed data, such potential model includes the symmetric trigonometric Rosen-Morse potential and some certain types of Pὂschl-Teller potential. Their inability to reproduce the observed data is due to the potential parameters that lack physical meanings. To make these types of potentials more useful and interesting, the present study combined the symmetric trigonometric Rosen-Morse potential and a type of Pὂschl-Teller potential and transformed the potential parameters to spectroscopic parameters to suit molecular study. The energy of the modified potential is applied to the study of some thermodynamic properties (enthalpy and heat capacity at constant pressure) for some molecules. The numerical results of the various thermodynamic properties of the modified potential reproduced experimental data for some molecules for the four molecules studied. The predicted results for each of the four molecules has average percentage deviation of less than one percent justifying an excellent agreement with the experimental data.